White hop shoot production in Slovenia : total phenolic, microelement and pesticide residue content in five commercial cultivars - Vidmar, Mateja (Array, 2019)
Harvesting of white hop shoots might be justified if they can be shown to be beneficial to human health. The aim of the present study is to determine the effects of hop cultivars and year of production on total phenolics, antioxidant potential, microelements and pesticide residues. Biomass per plant was highly variable among the cultivars (3.1-7.1 g dry mass per plant) and depended on hop cultivar and year (2009-2011). Total phenolics as chlorogenic acid equivalents (CAE) on dry mass basis varied from 0.60 to 1.80 mg/g, and showed significant effects across hop cultivar and year. The radical scavenging activities of the samples collected in years 2010-2012 ranged from 11 to 19 μg CAE.